Penguatan Karakter Anti-Bullying melalui Pendekatan Partisipatif pada Siswa SD dan SMP di Desa Ranosangia Kecamatan Toari - Agusman, Yudi; Rahma Nabila; Diki Pratama; Amida Datu; Dewa Ardhi Saputra Ahnur; Alan Syahril; Jingga Astri Ananta; Nurhikmah Abdullah; Puput Yuspitasari; Rahmad Hidayat; Riskawati; Risnawati; Silfia Ningsih; Trezzi Oliviya (LOSARI DIGITAL, 2025)
The community service program was designed to raise collective awareness of bullying while fostering a more positive school environment. The program was implemented through needs assessment, collaboration with schools, and the delivery of educational materials using visual aids, interactive discussions, games, and edutainment activities. The results indicate an increased understanding among students of the forms and impacts of bullying, greater willingness to share personal experiences in safe discussion spaces, and the internalization of values such as empathy, cooperation, and respect for diversity. Active student engagement was further supported by teachers and school leaders, who affirmed that the program aligned with existing character education efforts. In conclusion, although not supported by quantitative data, this participatory approach proved effective in enhancing anti-bullying awareness and encouraging a collective commitment to building a sustainable and conducive learning culture.